(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
This study aimed to show the significant relationships between emotion and behavior variables among throughout the behavioral modification learning processes in individuals with Autism Spectrum Disorder (ASD). A quasi- experimental research design pre- tests - post- test was realized. A total of 10 years old children with ASD level 1, who have been distributed into two groups, an experimental group (n= 5), whom a sensory integrated behavior program was applied and a control group (n=5), whom a behavioral modification “Stimulus”- “Response”- “Readjustment” (S-R) program has been applied. Results found through Mann-Whitney U Test and Pearson Correlation Test showed that there´re significant differences between both groups and, above all, great relationships are indicated between the emotional and behavioral variables found as a result of the learning process.